Integration of Religious Character Education Values of Santri at Dayah (Pesantren) - Nisak, Khoirun; Mubarak, Fadhil (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
This research aims to provide a description, analysis, and interpretation of the values and integration of religious character education values of santri at Dayah Ummul Ayman Samalanga Bireuen Aceh. Based on the research questions, the method used is a qualitative approach with a case study design. The research locus was chosen at Dayah Ummul Ayman Samalanga Bireuen Aceh, and the research sample consisted of santri and teachers at the dayah. The sampling technique used was purposive and snowball sampling. Data collection was conducted through observation, in-depth interviews, and documentation. Data were analyzed using the Miles and Huberman Interactive Qualitative Analysis Technique. The Miles and Huberman Interactive Qualitative Analysis Technique was performed by collecting data, displaying data, condensing data, and then drawing conclusions. The analyzed data were verified for their truth and validity through triangulation. The results of the study indicate that the religious character education values found are piety, earnestness, patience, courtesy, honesty, love of knowledge, and simplicity. The integration of religious character education values of santri is applied in the vision and mission of the dayah, in the dayah curriculum, and in dayah learning. These religious character values have implications for improving understanding and practice of religious values, shaping characters that are honest, patient, and polite, and encouraging earnestness and concern in activities.